Double‐blind, randomized controlled trial of therapeutic plasma exchanges vs sham exchanges in moderate‐to‐severe relapses of multiple sclerosis. Issue 4 (5th May 2020) - Brochet, Bruno; Deloire, Mathilde; Germain, Christine; Ouallet, Jean‐Christophe; Wittkop, Linda; Dulau, Cécile; Perez, Paul; Thevenot, Florian; De Sèze, Jérome; Zéphir, Hélène; Vermersch, Patrick; Pittion, Sophie; et al.
Abstract: Introduction: No randomized controlled clinical trial of therapeutic plasma exchanges (TPE) has yet been performed for moderate‐to‐severe relapses of multiple sclerosis (MS). Objective: To compare TPE to sham‐TPE in patients with a recent steroid‐resistant moderate‐to‐severe MS relapse. Methods: Patients presenting with an MS relapse of less than 2 months without improvement and 15 days after a course of steroids were randomized. Specific criteria were used for each relapse type to define moderate‐to‐severe disability. The primary endpoint was the proportion of patients with at least a moderate improvement based on objective and functional evaluation after 1 month. Results: Thirty‐eight patients were randomized. The intention‐to‐treat analysis included 14 patients in the TPE group and 17 in the Sham‐TPE group. The proportion of patients with at least moderate improvement at 1 month did not differ between the groups ( P = .72), although 57.1% of the TPE group had full recovery compared with 17.6% of the sham group. Considering optic neuritis (ON), a significant difference in the proportion of different levels of improvement was observed in favor of the TPE group ( P = .04). The combined Kurtzke's functional systems scores were significantly more improved in the TPE group than in the sham‐TPE group at months 1 ( P  < .01), 3 ( P  < .05), and 6 ( P  < .05). No major side effects were observed. Conclusions: A significant difference between TPE and Sham‐TPE at the primary endpoint was only observed in patients with ON. Neurological function improved significantly more often in the TPE group than in the sham‐TPE group.